The Effect Of Work Load And Burnout On Performance Employees With Mediation Job Satisfaction At Klungkung Regional General Hospital - Kadek Bayu Sastrawan; Ida Bagus Agung Dharmanegara; Putu Ngurah Suyatna Yasa (Global Researcher Network, 2022)
The hospital is a place of health care that must be managed properly. For this reason, hospital management must be better and more professional, especially HR management. One important role of human resource management is maintaining and improving employee performance. Employee performance can affect the achievement of company goals that have been set. The purpose of this study was to determine the effect of workload and burnout on employee performance mediated by job satisfaction. The sampling technique used in data collection is Probability Sampling using Simple Random Sampling. The sample used was 122 people from a population of 174 people. The results showed that workload had a negative effect on job satisfaction, and the relationship was not significant. Workload has a positive effect on employee performance and the relationship is significant. Burnout has a positive effect on job satisfaction, and the relationship is not significant. Burnout has a negative effect on performance, and the relationship is significant. Job satisfaction negatively affects nurses' performance, and the relationship is not significant.